Efficacy of rituximab on seizure control and cognitive symptoms in leucine‐rich, glioma‐inactivated 1 (LGI1) limbic encephalitis: a high‐density electroencephalography case study. Issue 5 (24th November 2020) - Cheli, Marta; Dinoto, Alessandro; Tommasini, Valentina; Ajčević, Miloš; Stella, Giulio; Catalan, Mauro; Stokelj, David; Sartori, Arianna; Manganotti, Paolo
Abstract: LGI1 encephalitis is an autoimmune disorder characterized by cognitive symptoms and seizures, which rarely respond to common antiepileptic drugs (AEDs). Rituximab (RTX) is a CD‐20‐depleting monoclonal antibody which has been used for the treatment of LGI1 encephalitis, however, its efficacy remains controversial. A 54‐year‐old woman came to our attention due to memory loss and gambling. Brain MRI revealed areas of bilateral hippocampal hyperintensity and LGI1 antibodies were found in both serum and cerebrospinal fluid. Immunotherapy with steroids was started, followed by intravenous immunoglobulins with partial improvement. The patient developed multiple generalized tonic‐clonic seizures. She was then administered intravenous rituximab with significant improvement for both cognitive symptoms and seizure control. High‐density EEG was recorded before treatment, seven days after the first dose and seven days after the second dose. Topoplot and power spectrum analysis were performed for each recording. Interictal epileptiform discharges, as well as theta power bands, were significantly reduced after each dose, while topoplot analysis showed reduced spreading over posterior and frontal electrodes for interictal epileptiform discharges of temporal origin. Our experience indicates that rituximab is a valid treatment for LGI1 encephalitis, demonstrating efficacy for both cognitive symptoms and seizure control. High‐density EEG could represent a novel, safe and reproducible method to study epileptogenesis in autoimmune limbic encephalitis.